IMPLEMENTASI AKUNTANSI BIAYA BERBASIS MICROSOFT EXCEL UNTUK MENINGKATKAN WAWASAN KEWIRAUSAHAAN SISWA SMAIT FITHRAH INSANI BALEENDAH - Sukawati, Renny; Rochmawati, Rochmawati; Rizal, Mochammad Fahru; Gustiani, Lia; Adhiyatunnisa, Najwa Latvia; Putri, Khania Tyana; Rayhan, Muhammad; Forlandito, Ryan Sebastian (Jurnal Abdimas Bina Bangsa, 2024)
Senior high school is a preparation period for students to have adequate skills to face challenges, whether in college, working, or when entering society. To strengthen understanding and improve abilities of students, it needs to be supported by technology-based facilities. Fithrah Insani Baleendah Bandung Integrated Islamic High School is an educational institution that focuses on the curriculum of the Ministry of Education and Culture of the Republic of Indonesia in the form of the Merdeka curriculum, with a typical FI curriculum, especially in learning Al-Quran, English, and computers, using multimedia and multi-methods. In the Merdeka curriculum, it is easy for students to obtain free sources of knowledge so that they are expected to be able to sort out good things to apply. The use of technology, namely Microsoft Excel, among students is important because it is useful for applying entrepreneurial insight in terms of cost accounting knowledge. Practically, the role of Microsoft Excel is being able to automate various production cost calculations, so that it will have a significant impact regarding increasing knowledge of students in using office tools and also their implementation in calculating costs